FORTIFICATION OF THE BIANG FISH (Ilisha elongata) ON THE SENSORY QUALITY OF TORN BREAD - Ahmad Suni; Sumarto Sumarto; Suparmi Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACT            The aim of this study was to determine the best quality characteristic of torn bread fortified with I. elongata flour with different concentrations of I. elongata using organoleptic parameters. The material used in this studied I. elongata purchased directly from fishermen in Selat Panjang, Kepulauan Meranti. The design of this studied an experiment with the manufacture of torn bread fortification of I. elongata flour with non-factorial complete random design consisting of 4 treatment level was P0 (0 g of I. elongata flour), P1 (12.5 g of I. elongata flour), P2 (25 g of I. elongata flour) and P3 (37.5 g of I. elongata flour) with sensory analysis included appearance, aroma, taste and texture. Panelists assessment results showed the best concentration was P1 treatment (12.5 g of I. elongata flour) with the appearance quality test results 8.47±0.05ab; the aroma 8.68±0.17b; taste 8.25±0.14bc; and rate of textures 7.91±0.18ab.Keywords: Concentration, fortification, I. elongata, quality, torn bread.